Aging and Narratives of Loss: A History of Social Suffering - Migliore, Sam; Dorazio-Migliore, Margaret (Anthropologica, 2014)
The notion of "loss" often appears as a common theme in both popular and academic discussions of aging. This focus on loss, however, tends to simplify or ignore important aspects of the phenomenon, including how people view themselves and their life experiences. In this article, we address how an individual life narrative can serve as: (1) a counter narrative to this notion of loss; and (2) a way of drawing attention to a variety of personal and structural factors that may complicate the experience of aging itself.